Computational modeling of biopotential fields in the female breast with and without tumour - Ng, Wan Kee (2008)
Most of us would agree that there is substantial room for the improvement of breast cancer detection, diagnostic and treatment. Preliminary analysis of the effects of mammographic screening suggests that early detection helps in achieving a real but small fall in overall mortality. Numerous sources suggest the efficacy of skin surface electrical potentials due to the underlying lesions. In the present studies, we presented a new approach; termed the Biofield Diagnostic System (BDS) might have the potential to augment the process of diagnosing breast cancer.